Les savoirs du poncho et de la cravate. Formations politiques et émergence des leaders indigènes en Bolivie - Claude Le Gouill (Les éditions de la Maison des sciences de l'Homme, 2015)
Several decades of struggle of indigenous peasant movements have contributed to reconfigure the Andean society. As symbolized by Evo Morales, the first president "native" of Bolivia, these movements have emerged a new elite: the "leader" natives. Trained within the community (traditional system of charges and Learning Knowledge Community authorities), these leaders have also access to other training systems in the fields of education (schools, training centers, universities) development (NGO trainings) and politics (parties, unions). They are characterized by their interface positions between the indigenous world and global society while defending an « organic» aspect of belonging to their community of origin, they are distinguished from "traditional" natives authorities by their capitals and knowledge acquired within the institutions of the outside world. It grows thereby a competition, but also a hybridization between the moral economy of the communities, defended by the indigenous bases, and the moral economy of new leaders activism.